Sosialisasi Pembelajaran Myob Berbasis Video Animasi Di Smk Negeri 1 Teluk Keramat - Sentiya, Novi; Roshani; Munandar (Jurnal Visi Pengabdian Kepada Masyarakat, 2025)
The learning process is a series of reciprocal relationships that take place between teachers and students in educational situations to achieve educational goals. This reciprocal relationship is the main condition for the learning process to take place. One of the goals of the learning process is behavior change, which includes changes in knowledge, attitudes and behavior. Achievement of the objectives of this learning process can be seen from the learning outcomes obtained as well as the attitudes and behavior of students in everyday life. However, various obstacles are still often encountered in implementing the learning process. Class XI Vocational School Accounting Computer Subjects, Institutional Accounting and Finance study programs are considered difficult by some students and can be intimidating to learn. Such an assumption is of course a big obstacle in the learning process, it can be said that students have lost before going to war. MYOB (Mind Your Own Business) is an accounting computer application program for working on the accounting cycle to produce financial reports. Students' problems in applying the MYOB accounting computer include setting accounts, setting taxes, linked accounts, recording initial balance data, recording cards, recording transactions, making adjustment journals and preparing financial reports which takes a long time to understand. Thus, animation-based learning videos were prepared to support student learning activities